CuOTeDsP nanotherapeutics enhance cuproptosis-mediated immunotherapy by modulating cholesterol metabolism in bladder cancer - Hai Cai; Panpan Xue; Siyuan Liu; Yaxin Ma; Xuemei Zeng; Shuangqian Yan; Ning Xu (Journal of Nanobiotechnology)
Abstract Elevated squalene epoxidase (SQLE) levels in bladder cancer cells drive abnormal cholesterol accumulation, contributing to malignancy, invasion, and resistance to immunotherapy. Here, we introduce a hollow CuO nanoparticle-based nanotherapeutic, termed CuOTeDsP, which is PEGylated and co-loaded with SQLE inhibitor terbinafine and disulfiram, for enhanced bladder cancer therapy through cholesterol metabolism modulation. CuO nanoparticles exhibit peroxidase-, catalase-, and glutathione oxidase-like enzymatic activities, along with biodegradability, resulting in elevated oxidative stress, alleviation of hypoxia, and responsive therapeutic release. Terbinafine reduces cholesterol levels in cancer cells by inhibiting SQLE, downregulating the expression of ATP7A and PD-L1, thereby promoting cellular Cu2+ accumulation and enhancing immune responses. Disulfiram further reacts with Cu2+ to form lethal bis(diethyldithiocarbamate)-copper complexes. Mechanistic studies reveal that CuOTeDsP induces cell death through a combination of cuproptosis and apoptosis, while simultaneously eliciting robust immune responses. In synergy with PD-1 monoclonal antibody, CuOTeDsP achieves a high tumor inhibition rate of 70% in a mouse bladder cancer model. This work highlights an effective strategy for bladder cancer by leveraging cuproptosis-driven immunotherapy and provides insights into the design of advanced nanotherapeutics. Graphical abstract